MARINE DEBRIS DAN MIKROPLASTIK: UPAYA MENCEGAH BAHAYA DAN DAMPAKNYA DI TEMPODE, DESA SALAMA, KABUPATEN MANGGARAI, NTT - Marlinda Mulu; Yohanes Wendelinus Dasor; Robertus Hudin; Vitalis Tarsan (Randang Tana - Jurnal Pengabdian Masyarakat, 2020)
Marine debris is a waste product found in the sea, whether intentionally disposed of or not. This type of plastic waste is the most commonly found in the sea.Plastic waste that found in the ocean will degrade into micro-plastics. Micro-plastics can cause harm to marine organisms and even reach humans through food chain events. In order to reduce the dangers and impacts, it is necessary to introduce the management of coastal areas as part of the ecosystem, through socialization activities to coastal communities. The results of the activities showed interest and positive responses from the community. In addition, the knowledge about the concepts of marine debris, micro-plastics and ecosystems and their relationships has also increased by i.e., of 76%.